Analisis Bentuk Atap Kanopi Gedung Kedokteran UBB Melalui Pendekatan Geometri Analitik Parabola - Dewi Rana; Virgiawan Virgiawan; Ananda Dwi Putri; Siska Amelia; Septiana Nadine; Cantia Purnawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
A parabola is a curve that consists of points that are equidistant from a fixed point (focus) and a fixed line (directrix). This study aims to analyze the shape of the canopy roof of the UBB Medical Building using an analytical geometry approach on parabolas. The method used is a quantitative descriptive based on visual documentary online and proportional estimates against comparative objects. The parabola model is constructed from three key points and visualized using GeoGebra. The results show that the shape of the canopy can be accurately represented through the equation of a parabola, with a symmetrical and aesthetic structure. This research proves that mathematical concepts can be practically applied in architectural design.